Three Level Boost Inverter with Reduction Stress Voltage of Capacitor - Tran, Thị Quỳnh Như; Nguyen , Thanh Long; Le, Văn Thiếp; Do, Đức Trí (Journal of Technical Education Science, 2022)
In this paper, a new topology and pulse-width modulation (PWM) strategy for the three-level quasi-switched boost T-type inverter (TL-MqSBT2I) to reduce stress voltage of capacitor is presented. The Shoot through (ST) state is inserted into zero vector in order not to affect the output voltage. The new topology of intermediate network is also presented to improve the boost factor and voltage gain. As a result, the voltage stress on power devices like capacitors, diodes, and power switches is decreased, significantly. Shoot through pulse control method can decrease voltage stress on capacitor up to 40% as compared to the traditional control method when the duty cycle D0 is 0.15 and duty cycle D1 is 0.7. By controlling the technique of alternating short-through between impedance source network and T-Type inverter. The operation principle and overall control strategy for this configuration are also detailed. The simulation is implemented with the help of PSIM software to demonstrate the accuracy of this strategy.